Chemical braking exhibited by ethynylhelicene (M)-nonamer in solution: Competitive reaction system of self-catalysis to form double-helix and approach towards equilibrium to form random-coil. Issue 19 (11th May 2017) - Sawato, Tsukasa; Yagi, Atsushi; Arisawa, Mieko; Yamaguchi, Masahiko
Abstract: Chemical braking occurs in a dilute solution during a structural change of ethynylhelicene ( M )-nonamer from the metastable double-helix state to the random-coil state, being at equilibrium, where the reaction is initially rapid and then substantially retard. The chemical braking is derived from the competitive chemical reaction system in dilute solution: An energetically uphill self-catalytic reaction to form double-helix and the downhill reaction to form the random-coil. Graphical abstract: Highlights: Ethynylhelicene ( M )-nonamer in dilute solution exhibits chemical braking. The phenomenon is derived from the competitive reaction system. The chemical braking provides a novel mechanism for the negative feedback.